Problemas de aritmética em tempos da aritmética intuitiva: uma análise em livros didáticos (1890-1930) - Pavarin, Karina Cristina Dos Santos [UNIFESP] (2020)
This master's thesis is based on the perspective of cultural history. Discusses the use of arithmetic problems in times of the intuitive method. Thus, when looking for works that contributed to the understanding of that moment, Oliveira's thesis (2017) was found that analyzes, among pedagogical documents, textbooks and highlights elements of a new knowledge, Intuitive Arithmetic. It was then decided that, from Oliveira (2017), the same five textbooks highlighted by him would be examined, deepening the discussion on arithmetic problems. To guide the research, the following question was raised: What are the purposes of using arithmetic problems in Intuitive Arithmetic? For the development of the study, the methodological research steps described by Valente (2018) were used: recompilation of teaching experiences, comparative analysis of teachers' knowledge, systematization and use of knowledge as knowledge. During the stage called recompilation of teaching experiences, observation and description were used, research procedures cited by Burke (2016). To carry them out, it was necessary to have a thorough look in search of approximations and distances from the works. Four purposes were identified: Explore, Instruct, Apply and Verify. However, in Intuitive Arithmetic, the purposes of Instruct and Apply form a dyad, dialogue with each other and have a central role in the characterization of Intuitive Arithmetic.